Sodium-Glucose Cotransporter-2 Inhibitors and Cardiovascular Protection Among Patients With Type 2 Diabetes Mellitus: A Systematic Review - Richard K. Yankah; Eric K. Anku; Vinay Eligar (Journal of Diabetes Research)
Conclusion: SGLT2 inhibitors have beneficial cardiovascular effects in patients with T2DM and should be incorporated into their management.